Bacillus thuringiensis growth and toxicity: basic and applied considerations - Avignone Rossa, Claudio Adolfo (1995)
Despite the known importance of the composition of culture media and culture conditions on Bacillus thuringiensis growth and toxicity, very few reviews are concerned with this subject. This article reviews some aspects of the microbiology of Bacillus thuringiensis, and how toxicity is affected by the composition of growth media and bioreactor operation.